PENGARUH PROMOSI DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN VOUCHER PAKET DATA INTERNET DI PT. DISTRIBUSI VOUCHER NUSANTARA - Acip Sucipto; Hasanudin; Rama Rosadi; Rizky Muyasar; Herdian Farisi (Journal of Principles Management and Business, 2026)
This study examines the influence of promotional strategies and pricing mechanisms on retailers' purchasing decisions within the business-to-business (B2B) distribution ecosystem of internet data voucher packages. The research was conducted at PT Distribusi Voucher Nusantara (PT DIVA), an authorized distributor serving retail partners across Bogor Regency, Indonesia. A quantitative survey approach was employed using proportional random sampling, with data collected through structured questionnaires administered to active retail partners. The data were analyzed using multiple linear regression supported by validity, reliability, and classical assumption tests. The findings reveal that both promotional strategies and pricing have positive and significant effects on retailers' purchasing decisions, both individually and simultaneously. These results indicate that effective promotional programs combined with competitive pricing play a crucial role in strengthening retailers' purchasing intentions and enhancing distributor–retailer relationships in the B2B market. This study contributes to the literature on B2B marketing by highlighting the strategic importance of promotion and pricing in the telecommunications distribution sector and provides practical implications for distributors seeking to improve retail partner engagement and purchasing performance within Indonesia's rapidly evolving digital economy.